2013
DOI: 10.1177/1753193413512222
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome (20 to 33 years) of radial shortening osteotomy for Kienböck’s lunatomalacia

Abstract: Radial shortening osteotomy (RSO) as treatment for Kienböck's disease usually improves patient symptoms for several years. Four small series have also shown that the effect may last for decades, but only two studies have used a patient-based assessment. We examined 16 patients, with a mean age at operation of 32 years, evaluating clinical and radiological results at a mean 25 (range 20 to 33) years after surgery. Three patients had progressive lunate collapse, of whom one patient needed a silicone implant arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Examples of such procedures are use of the vascular pedicle of the distal radius of bone flap for filling of the lunate bone, radial shortening osteotomy, and osteotomy of the capitate bone at pars lumbalis. [1214] Litchman classified Kienböck disease into 4 stages. In the IIIb-IV stage, the features of lunate bone necrosis are observed, for example, collapse of the lunate bone, scaphoid bone rotation, proximal displacement of the capitate bone, changes of carpal bone height, and features of wrist osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such procedures are use of the vascular pedicle of the distal radius of bone flap for filling of the lunate bone, radial shortening osteotomy, and osteotomy of the capitate bone at pars lumbalis. [1214] Litchman classified Kienböck disease into 4 stages. In the IIIb-IV stage, the features of lunate bone necrosis are observed, for example, collapse of the lunate bone, scaphoid bone rotation, proximal displacement of the capitate bone, changes of carpal bone height, and features of wrist osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with more than 10 years of follow-up on average report mean (Quick)DASH scores between 6.1 and 14 and pain scores between 0.2 and 3.0 after radial shortening osteotomy (►Table 4). [21][22][23][24][25] Luegmair et al found that patients had poorer physical function when the dominant side was affected. 25 We found no such difference by hand dominance.…”
Section: Discussionmentioning
confidence: 99%
“…X-rays were performed in a standardized manor concerning wrist extension, forearm rotation, and radial-ulnar deviation. The radiographs for these examinations were a Pa view (dorsopalmar view), a lateral view, and an oblique view to provide additional information as to the internal structure of the lunatum (16)(17)(18).…”
Section: Objective Measurementsmentioning
confidence: 99%
“…The following were radiologically measured in both wrists: ulnar variance, radioscaphoid, and scapholunate angles (19); metacarpal height ratio (metacarpal index) (20); ulnar translation ratio (19); Ståhl index (relation of height to breath of the lunate bone as a percentage); and lunate-covering ratio (calculated by dividing the amount of the lunate supported by the radius by complete radioulnar width of the lunate) (17). The metacarpal height ratio was calculated by dividing the height of the carpus by the length of the middle-finger metacarpal (normal: 0.54 ± 0.03).…”
Section: Objective Measurementsmentioning
confidence: 99%